METHODS OF CORRECTION BY SPEECH THERAPY IN ESTABLISHING OF VERBAL COMMUNICATION FOR NON-VERBAL CHILDREN IN PRE-SCHOOL AGE - Anosko, Lucija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
According to the experience of many speech therapists, lately, there is a growing number of non-verbal children. Such a tendency is observed not only in special pre-school education institutions but also in general pre-school institutions. These children need the help of a speech therapist who can determine the speech therapy conclusion and choose the methods of correction. The goal of the research is to explore and analyze the effectiveness of the methods of corrections by speech therapy in the creation of verbal communication for non-verbal children in pre-school age. The correction activities consist of several stages, and as a result, children learn the skills of verbal communication and according to their abilities, use this type of communication in their daily life. Conclusions. The corrective work by speech therapy is done in a way that the speech disorder in pre-school age is eliminated or minimized. The complex impact can bring optimal results in the correction of speech disorders.